Adjusting blood redistribution to suppress flow disturbances of hemodialysis arteriovenous fistula: a computational fluid dynamics analysis - Li, Yong-Jiang; Hou, Hui-Min; Liu, Zheng; Xue, Chun-Dong; Na, Jing-Tong; Meng, Qing-Mei; Li, Zhe-Yuan; Sun, Hai-Yang; Wu, Yu-Lin; Liu, Shu-Xin; Qin, Kai-Rong (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe dramatic hemodynamic disturbances induced by arteriovenous fistula (AVF) creation are universally acknowledged as the triggering factors for AVF dysfunction. The postoperative blood redistribution is greatly relevant with the flow disturbances of the AVF, such as disturbed flow, low wall shear stress (WSS), and oscillating WSS. However, the relationship between blood redistribution and hemodynamic disturbances of AVF remains unexamined. The role of clinically observed retrograde blood flow at the distal radial artery is rarely understood.MethodsIn this study, an idealized AVF model was developed with clinical data collected from end-stage renal disease patients. By considering the postoperative blood redistribution, the influence of the blood flow rate ratio on hemodynamic disturbances is numerically studied.Results and discussionThe results demonstrate that the creation of the AVF can result in flow disturbances such as vortex, reciprocating flow, and low and reciprocating WSS, whose occurrence regions are consistent with clinical observations. The flow rate ratio and flow direction of the distal radial artery play important roles in regulating the low-WSS area within the AVF anastomosis, especially for the flow rate of the proximal radial artery (PRA). Moreover, the clinically observed retrograde blood flow in the distal radial artery contributes to the reduction in the low-WSS area, revealing a compensatory mechanism. This study can provide valuable insights for understanding the effect of blood redistribution on flow disturbances in the AVF, as well as the compensatory role of the retrograde distal radial artery flow, which helps optimize blood redistribution for a well-functioning AVF.